Determining Fracture Pressure Gradients from Well Logs - K. I, Udo; N. J, George; A. O, Akankpo; G. B, Azuoko; M.U, Aka (International Journal of Advanced Geosciences, 2020)
Fracture pressure gradient is one of the essential parameters used in determining mud weight profiles during drilling operations. We have determined fracture pressure gradients from well logs obtained from three producing wells in Onshore Niger Delta using an empirical model. Key logs needed for the prediction were conditioned and quality controlled to meet the standard required for reliable results. The true vertical stress, normal compaction trend and compressional shale velocity trends were generated from the logs (density and sonic logs). Poisonâ€™s ratio was obtained from compressional and shear wave velocities derived from sonic log. Pore pressures in the three wells were then predicted using Eatonâ€™s Method. The predicted pore pressures, overburden pressures and poisonâ€™s ratio were used to determine fracture pressures using Ben Eatonâ€™s Model. Results showed that there is a suitable drilling margin at all depths only in well G-005. Drilling well A-001 to a depth of 10962.81 ft and K-001 to a depth of 12626.9 ft will fracture the formations because the fluid pressures at those depths approximate the fracture pressures of 8536.7psi and 9506 psi with corresponding gradients of 0.78 psi/ft and 0.75 psi/ft respectively. The implication is that drilling deeper in the field will results in very low seal capacity magnitudes, thereby presenting a higher risk of top-seal failure.Â Â